SOSIALISASI UNDANG-UNDANG INFORMASI TRANSAKSI ELEKTRONIK (Pencegahan Informasi Hoax di tengah Covid – 19) - Yuhandra, Erga; Akhmaddhian, Suwari; Fathanudien, Anthon; Budiman, Haris (Jurnal Pintar Abdimas, 2021)
The rapid development and advancement of Information Technology has led to changes in the activities of human life in various fields which have directly influenced the birth of new forms of legal action, the use and utilization of Information Technology must continue to be developed to maintain, maintain and strengthen national unity and integrity based on Legislation in the national interest, that the use of Information Technology plays an important role in trade and national economic growth to create public welfare. The purpose of this service focuses more on teenagers, both boys and girls, while other targets are the objectives of holding this counseling, namely the community in general. The approach method used in this Community Service is through the workshop approach method, lectures then at the end of the event a question and answer session is held, with this question and answer the community is given the opportunity to ask questions according to the theme of extension, or the community can ask questions outside the predetermined theme. The benefit of holding legal counseling in Margasari Village, Luragung District, Kuningan Regency, West Java Province is to create a better legal awareness of the community so that every member of the community realizes and lives up to their rights and obligations as citizens and creates a legal culture in attitudes and behaviors that are aware, obedient, and obey the law and can understand good information in the use of gadgets and social media in the digital era as it is today.